The role of corporate governance in reducing illicit financial outflows In South Africa - Ramparsad, Tia-Schae (University of the Witwatersrand, Johannesburg, 2024)
Illicit financial outflows have emerged as a significant concern in South Africa, impeding economic growth, exacerbating social inequality, and undermining the country's developmental efforts. This research report aims to investigate the crucial role of corporate governance in reducing illicit financial outflows in South Africa. By examining the factors contributing to these outflows and exploring the effectiveness of corporate governance mechanisms, this study provides insights into how ethical and accountable business practices can contribute to curbing illicit financial activities. This research report highlights significant corporate scandals in South Africa, underscoring the imperative need for strong corporate governance practices to prevent illicit financial outflows. Despite sterling efforts, various areas require improvement and pose distinct challenges. Enforcing corporate governance practices demands adequate resources and capacity within regulatory bodies. Additionally, challenges include the lack of transparency in beneficial ownership and limited shareholder activism, both hindrances to curbing illicit financial outflows. Collaborative efforts are paramount, with stakeholders, including regulatory bodies, companies, shareholders, and the government, working together to fortify corporate governance frameworks, enhance regulatory oversight, foster ethical business conduct, and elevate public awareness. Critical areas of focus encompass strengthening internal controls, ensuring board independence and composition, addressing executive compensation structures, promoting shareholder engagement, enhancing risk management and internal control mechanisms, and improving regulatory oversight and enforcement. Moreover, fostering collaboration among stakeholders and upholding ethical standards are essential elements in curtailing illicit financial outflows, ultimately fostering transparency, accountability, and sustainable economic development in South Africa.
A research report submitted in fulfillment of the requirements for the Master of Laws, In the Faculty of Faculty of Commerce, Law and Management, School of Law, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; CORPORATE GOVERNANCE; ILLICIT FINANCIAL OUTFLOWS; CORPORATE ACCOUNTABILITY; SDG-8: Decent work and economic growth